Interaksi antara Bakteri Endofit dan Bakteri Perakaran Pemacu Pertumbuhan Tanaman dalam Menekan Penyakit Layu Bakteri pada Tomat - Abdjad Asih Nawangsih; Fitri Fatma Wardani (Jurnal Fitopatologi Indonesia, 2014)
One of the factors affected production of tomato is the incidence of bacterial wilt disease caused by Ralstonia solanacearum. An alternative control to manage the disease which is environmentally friendly is the use of biocontrol agents. Application of endophytic bacteria (Staphylococcus epidermidis BC4) and plant growth promoting rhizobacteria (Pseudomonas fluorescens RH4003 and Bacillus subtilis AB89) as biocontrol of tomato bacterial wilt was expected to be an alternative method. The objective of this study is to evaluate the interaction among endophytic bacteria and PGPR to suppress the development of bacterial wilt disease (R. solanacearum) and promoting the growth of tomato. Bacterial treatment which caused the highest suppression on disease incidence was single application of P. fluorescens RH4003. Disease index caused by S. epidermidis BC4 and P. fluorescens RH4003 applied individually was up to 41.18 dan 45.88%, respectively. Interaction between the endophytic bacteria and both of the PGPRs were antagonistic.